The Influence of Digital Promotion, Product Quality and Product Halal Commitment on Marketing Performance of Meatball Small and Medium Enterprises (SMEs) in Bantul Regency - Annisa Akmala Dewi; Febrian Wahyu Wibowo; Baiq Ismiati; Al Haq Kamal (Journal of Islamic Economics (JoIE), 2026)
Introduction: Small and Medium Enterprises (SMEs) play a vital role in the Indonesian economy, particularly in Bantul Regency, which holds significant potential in the food processing sector, including meatballs. However, intense competition requires effective marketing strategies to improve marketing performance. This study aims to determine the effect of digital promotion, product quality, and Halal Product Commitment on the marketing performance of meatball SMEs in Bantul Regency. Research Methods: This study employed quantitative research methods. A sample of 80 respondents was selected using a probability sampling method with a proportional stratified random sampling technique. Data collection used a questionnaire processed with SPPS 22, and data analysis used multiple linear regression. Results: The results show that digital promotion, product quality, and Halal Product Commitment collectively have a significant effect on marketing performance, with a significance value of <0.05. Conclusion: By optimizing digital promotion, maintaining product quality, and ensuring halal product compliance, meatball SMEs in Bantul Regency can significantly improve marketing performance and achieve sustainable business growth.